The trauma still goes on…: The multigenerational legacy of Northern Ireland's conflict. (October 2013) - Downes, Ciara; Harrison, Elaine; Curran, David; Kavanagh, Michele
Numerous studies have been conducted internationally on the subject of multigenerational trauma; however, little is currently known about its existence in the context of the Northern Ireland conflict. The present study explored the outcomes of and mechanisms through which the trauma of one generation impacts on subsequent generations in this context. Using an Interpretative Phenomenological Approach (IPA), this study examined the subjective experiences, beliefs and perceptions of four mothers from Northern Ireland, all of whom had endured trauma during their childhoods. Three main master themes emerged: 1. "Attempting to cope" addressed how the trauma was dealt with, and how these efforts can be the very mechanisms through which multigenerational trauma occurs. Examples include hiding the truth, seeing the truth as dangerous, and knowing and not knowing about the trauma; 2. "The trauma still goes on" highlighted the negative outcomes and consequences of the traumatic experiences within the family such as delayed impact, symptoms and anger; and 3. "Strength through adversity" included the more positive outcomes of their experiences, such as finding meaning through suffering and making efforts to stop the cycle. The results are discussed in terms of the existing theories on multigenerational trauma, and implications for practice are explored.